Heterogeneity in the Drosophila gustatory receptor complexes that detect aversive compounds. Issue 1 (December 2017) - Sung, Ha; Jeong, Yong; Lim, Ji; Kim, Hyeyon; Oh, Soo; Hwang, Sun; Kwon, Jae; Moon, Seok
Abstract Animals must detect aversive compounds to survive. Bitter taste neurons express heterogeneous combinations of bitter receptors that diversify their response profiles, but this remains poorly understood. Here we describe groups of taste neurons inDrosophila that detect the same bitter compounds using unique combinations of gustatory receptors (GRs). These distinct complexes also confer responsiveness to non-overlapping sets of additional compounds. While either GR32a/GR59c/GR66a or GR22e/GR32a/GR66a heteromultimers are sufficient for lobeline, berberine, and denatonium detection, only GR22e/GR32a/GR66a responds to strychnine. Thus, despite minimal sequence-similarity, Gr22e andGr59c show considerable but incomplete functional overlap. Since the gain- or loss-of-function ofGr22e orGr59c alters bitter taste response profiles, we conclude a taste neuron's specific combination ofGrs determines its response profile. We suspect the heterogeneity ofGr expression inDrosophila taste neurons diversifies bitter compound detection, improving animal fitness under changing environmental conditions that present a variety of aversive compounds. Taste sensilla areDrosophila sensory organs containing taste neurons, which have differential tuning for bitter compounds. Here, the authors systematically examine what combinations of gustatory receptor genes confer a specific taste response profile in different bitter taste neurons.